Soil cover on nutrient concentration in an agroecosystem in Napo, Ecuador - Abril Saltos, Ricardo Vinicio (2023)
Introduction. Nutrient loss in different soil cover generates a decrease in productivity in agroforestry systems in tropical forests. Objective. To determine the effect of soil cover over a two-year period on nutrient concentrations in the agroecosystem of the Amazonian Research and Production Experimental Center. Materials and methods. This study was conducted at the Amazonian Research and Production Experimental Center in Napo, Ecuador. Two plots of primary forest were established with the following soil covers: a) guava (Inga sp.) and b) melastomataceae. Two random soil samplings were conducted, one in 2019 (four samples per cover) and another in 2021 (six samples per cover). Concentrations of nitrogen, phosphorus, potassium, calcium, and organic matter were analyzed. An analysis of variance was applied to determine significant differences between the soil coverages and sampling periods. Pearson correlation analysis was performed to determine relationships between the concentrations of different nutrients. Results. Significant differences (p<0.05) were observed for soil covers in concentrations of organic matter and phosphorus, which were higher in the melastomataceae plot. In 2021, significant differences were observed for potassium, phosphorus, and nitrogen concentrations. The year x cover interaction in guava cover showed an increase in nutrient concentrations after two years. Significant correlations were found between potassium concentrations and the other nutrients, as well as between organic matter and nitrogen concentrations. Conclusion. Soil cover influenced nutrient concentrations, which varied between years. The primary forest exhibited the highest nutrient loss, and the Inga cover showed an increase in nutrient concentrations over time.